18th International Conference on Pattern Recognition (ICPR'06) 2006
DOI: 10.1109/icpr.2006.97
|View full text |Cite
|
Sign up to set email alerts
|

A Maximum-Likelihood Approach to Symbolic Indirect Correlation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Polygram matches between the sample in question and a set of labeled reference words are used to derive the query likelihood for each class, P(query|class). 3,7 Then, like character-/sub-character recognition schemes, SIC builds a lexical transcript by imposing grammatical constraints on the assigned polygrams. Unlike these methods, however, unconstrained partial word matching does not rely on the error-prone segmentation of the query into letters or strokes.…”
Section: Figure 2 the Classifier Can Identify The Partial Word Matchmentioning
confidence: 99%
“…Polygram matches between the sample in question and a set of labeled reference words are used to derive the query likelihood for each class, P(query|class). 3,7 Then, like character-/sub-character recognition schemes, SIC builds a lexical transcript by imposing grammatical constraints on the assigned polygrams. Unlike these methods, however, unconstrained partial word matching does not rely on the error-prone segmentation of the query into letters or strokes.…”
Section: Figure 2 the Classifier Can Identify The Partial Word Matchmentioning
confidence: 99%
“…Later investigations showed that in the presence of excessive noise, the sub-graph isomorphism based approach to the second-level matching requires an unreasonably large reference set [8,9]. A maximumlikelihood approach [10] avoids this computational bottleneck in the second-level matching. Since this method seems promising for Arabic recognition, we describe in some detail how we build candidate solutions to the query; interested readers will find full technical details in [10,11].…”
Section: Arabic Character Recognitionmentioning
confidence: 99%
“…However, there are many spurious matches as well. Our second-level matching process, described in [10] is shown to be robust against a large number of spurious matches but at the expense of increased computation time. Therefore, we plan to explore a post-processing approach to eliminate some bad matches.…”
Section: Arabic Character Recognitionmentioning
confidence: 99%
See 1 more Smart Citation